Respuesta :
The procedure for an inverse is to interchange x and y and solve for y
x = -3/y + 4 I'm solving this as it is written and not x = -3/(y + 4) Subtract 4
x - 4 = -3/y
y(x - 4) = - 3
y = -3/(x - 4)
If you did mean y = - 3/(x + 4) then the inverse would be
x = - 3 / (y + 4)
x*(y + 4) = -3
y + 4 = -3/x
y = -3/x + 4
Amazing! The inverse is the same as the original question.
x = -3/y + 4 I'm solving this as it is written and not x = -3/(y + 4) Subtract 4
x - 4 = -3/y
y(x - 4) = - 3
y = -3/(x - 4)
If you did mean y = - 3/(x + 4) then the inverse would be
x = - 3 / (y + 4)
x*(y + 4) = -3
y + 4 = -3/x
y = -3/x + 4
Amazing! The inverse is the same as the original question.